IMPROVING THE TECHNICAL AND TACTICAL TRAINING OF YOUNG FOOTBALL PLAYERS THROUGH MOVEMENT GAMES (Proximus Journal of Sports Science and Physical Education, 2024)
The article is dedicated to studying the effectiveness of using active games in the educational and training process of young footballers during initial training. The structure and content of training camps for footballers involved in initial training groups are considered